POLITICAL AESTHETICS OF URBAN ENCOUNTERS: ON DIFFERENCE AND THE FEELING OF SAFETY - Pathirane, Henrik (The Nordic Journal of Aesthetics, 2022)
Aesthetics and politics are intertwined in our everyday encounters and even nonverbal encounters are negotiations of meanings, values, and means of representation. The aesthetic political negotiation of urban encounters is politics beyond consensus and dissensus: an open-ended process of altered perception. Perception of difference, a feeling of safety, and a form of distanciation are required for the political potential to be actualized. This article begins by discussing urban encounters and the notion of politics. Politics takes place in the public sphere and is actualized in political negotiations, which in ephemeral encounters take the form of pondering, or hermeneutic understanding and judgment. The second section discusses the prerequisites: safety, distance, and difference. Two points are made. Firstly, the political encounter contains a practical-ethical demand for effort in our everyday life. Secondly, training aesthetic sensibility assists in this pursuit. This article is an example of an approach of inquiry that can be called political aesthetics.